Entrepreneurship and Local Economic Development : A Comparative Perspective on Entrepreneurs, Universities and Governments - Dallago, Bruno; Tortia, Ermanno; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
This book focuses on the nature and role of entrepreneurship in modern developed and emerging economies and societies, its relation to governments and universities, and its role in the often-forgotten informal economy. The aim is to position entrepreneurship in the post-crisis context and explore how its relation to universities and governments contributes to explain the countries$1 (Band territories$1 (Bgrowth performance and resilience or vulnerability to the crisis. The accent is particularly on processes and patterns at local level and in small and medium-sized enterprises in local economic systems and districts, local systems of innovation, and the types and configurations of innovation these give origin to. With globalization, entrepreneurship has become fundamental for the competitiveness of territories and countries, for policy management and for development. The local dimension is fundamental because of agglomeration economies and effects, the advantages of proximity and the nature of knowledge and information. Furthermore, territories carry to the centre-stage tacit knowledge, localized social capital, embeddedness and interpersonal relations as fundamental components of endogenous socio-economic development and of the competitiveness of territories. When local systems are connected in a horizontal network, they contribute to the strength of national and international systems. To play a constructive role from this perspective, entrepreneurship must avoid local entrenchment and support the local economy to upgrade and be competitive. To do this, the entrepreneurs$1 (Binteraction and alliance with universities and governments is a must for those countries and localities wanting to emerge. This requires that enterprises, universities and governments create synergies and spillovers to their mutual advantage.s
Introduction: entrepreneurs, universities and governments Ermanno Tortia --PART I Entrepreneurship and its frames --1 Entrepreneurship, the entrepreneur and the territory: an introduction Bruno Dallago 2 Are anchor institutions the answer to the prayers of small business owners in the UK? David Smallbone and John Kitching 3 Comparative analysis of innovation policy and market quality: lessons from Russia and Japan Satoshi Mizobata 4 Different types of informal entrepreneurs in fragile transitional contexts: case-based evidence in Russia Alexander Chepurenko 5 Re-stimulating Chinese entrepreneurship through the mixed ownership reform Zhikai Wang 6 Determinants of the internationalization of Chinese enterprises: evidence from firm-level survey data Jiadong Pan and Wen Xiao 7 Managerial quality, business liberalization and corruption: the case of Turkey Maria Litvinova and Maria Luigia Segnana --PART II Entrepreneurship, universities and governments --8 Innovation modes and knowledge relations: the learning match between university and enterprises from a regional perspective Peter Nielsen 9 Creative workers in Europe: is it a reserve of the Would-Be Entrepreneurs? A cross country comparison Csaba Mak, Mikls Illssy and Andrs Borbly 10 Graduate entrepreneurship support: what higher education institutions do, and how government can support them. Lessons from Hungary and Ireland Andrea-Rosalinde Hofer and Peter Baur 11 The effect of government intervention on entrepreneurship: empirical evidence from China Wenjie Zhu and Zhikai Wang --PART III The territory as context --12 The role of a local university in regional development: the case of Regensburg Joachim Mller and Christoph Rust 13 Academic spin-offs and the innovative city: universities role in the entrepreneurial ecosystem of Boston Alessandro Baroncelli and Matteo Landoni 14 Native and immigrant entrepreneurship: costs of doing business and local liabilities Simone Guercini and Matilde Milanesi Conclusion: the triple helix, social impacts and beyond Ermanno Tortia
Includes bibliographical references and index.
Also available in print format.
Keywords: BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Labor; Entrepreneurship; New business enterprises; Small business; Community development; Rural development; Global Financial Crisis, -- 2008-2009.; Electronic books